2019
DOI: 10.1016/j.jcol.2019.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiologic criteria and predictors of survival of rectal cancer among Egyptians in Delta region

Abstract: Background  Colorectal cancer represents a global health problem. Rectal cancer in particular is increasing and is believed to carry a unique epidemiologic and prognostic criteria. Method  We herein study retrospectively the data of 245 patients from a tertiary center in Egypt. Clinico-epidemiologic criteria and predictors of survival are analyzed. Results  The disease affects younger population without sex predilection. Prognosis is affected by age, nodal stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
(18 reference statements)
1
1
0
Order By: Relevance
“…In our study, there was a significant correlation between local recurrence and tumor size and neoadjuvant chemoradiation. Our 5 years incidence of local recurrence matched with the study of Metwally et al [7] that included 245 patients who registered at the Oncology Center, Mansoura University (OCMU) from 2006 to 2017, local recurrence incidence was 15.8%).…”
Section: Discussionsupporting
confidence: 71%
“…In our study, there was a significant correlation between local recurrence and tumor size and neoadjuvant chemoradiation. Our 5 years incidence of local recurrence matched with the study of Metwally et al [7] that included 245 patients who registered at the Oncology Center, Mansoura University (OCMU) from 2006 to 2017, local recurrence incidence was 15.8%).…”
Section: Discussionsupporting
confidence: 71%
“…Most of cases presented with locally advanced stage is due to lack of screening and delay in diagnosis because anorectal bleeding that represents 45% of symptoms of CRC is initially thought to be due to hemorrhoids (11) . Management of locally advanced rectal cancer is crucial to achieve better survival rate as survival of CRC is highly depended on stage at presentation, in Egypt the median overall survival is 2 years (stage I 44 months; stage IV 8 months) (12) . The role of multimodality treatment in LARC is to decrease recurrence rate and improve survival (13) .…”
Section: Discussionmentioning
confidence: 99%
“…2 CRC survival rates are highly dependent upon the disease stage at diagnosis: at the localized stage, it is 90%; 70% at regional disease, and 10% for patients diagnosed with distant metastasis. 3 Inflammatory bowel disease (IBD), considered a risk factor for CRC, represents 1-2% of all CRC cases. Longitudinal investigations have shown that the severity of colonic inflammation, the length of bowel involvement, and the presence of primary sclerosing cholangitis are all indicators of the development of CRC.…”
Section: Introductionmentioning
confidence: 99%